Materials correspondence of K. V. Kharlampovich and M. S. Hrushevsky as a source on the history of scientific elite 20-30s of the twentieth century - Lina Medovkina (Cхід)
This article investigates materials correspondence academician of theRussianAcademyof Sciences and academician of the Ukrainian Academy of Sciences, K. V. Kharlampovich historian and academician M. S. Hrushevskogo. It is noted that academician M. S. Hrushevsky took an active part in the protection, moral and material support of academician K. V. Kharlampovich years in exile, and also try to get him back to Ukraine and restoration him of the ranks of full members of the Ukrainian Academy of Sciences.